Molecular Signaling Interactions and Transport at the Osteochondral Interface: A Review - Oliveira Silva, Mateus; Gregory, Julia L.; Ansari, Niloufar; Stok, Kathryn S. (Frontiers in Cell and Developmental Biology, 2020)
Articular joints are comprised of different tissues, including cartilage and bone, with distinctive structural and mechanical properties. Joint homeostasis depends on mechanical and biological integrity of these components and signalling exchanges between them. Chondrocytes and osteocytes actively sense, integrate, and convert mechanical forces into biochemical signals in cartilage and bone, respectively. The osteochondral interface between the bone and cartilage allows these tissues to communicate with each other and exchange signalling and nutritional molecules, and by that ensure an integrated response to mechanical stimuli. It is currently not well known how molecules are transported between these tissues. Measuring molecular transport in vivo is highly desirable for tracking cartilage degeneration and osteoarthritis progression. Since transport of contrast agents, which are used for joint imaging, also depend on diffusion through the cartilage extracellular matrix, contrast agent enhanced imaging may provide a high resolution, non-invasive method for investigating molecular transport in the osteochondral unit. Only a few techniques have been developed to track molecular transport at the osteochondral interface, and there appear opportunities for development in this field. This review will describe current knowledge of the molecular interactions and transport in the osteochondral interface and discuss the potential of using contrast agents for investigating molecular transport and structural changes of the joint.